Indeterminism and Slowdown of the World Economy Growth and Their Consequences for the Global Development on the Contemporary Stage - Revenko Anatolii (Міжнародні відносини: теоретико-практичні аспекти, 2020)
The aim of the investigation is the analysis of growth slowdown and indeterminism (uncertainty) in the measures of the world economy, consequences clarification for the global development, which stipulates the consideration of the international economical tendencies, discussions around the situation with the international trade and restoration of the financial instability. Methodology of the research is based on the general scientific methods and on specialized methods of the economic analysis. Argumentation of theoretical positions and conclusions is done on the system approach basis with using the following methods: historical-logical, structural-functional and comparative analysis. The thesis that in 2015 UN run three main global programs (Purposes of constant development, Addis Ababa program and Paris climate agreement) is substantiated which as of today have faced a weakening of multilateralism, destabilization and large-scale uncertainties surrounding the world economy, to which the effects of the COVID-19 pandemic on health, the economy and social activities are now added. It is proved that that the expected slowdown in the world economy has been exacerbated by the pandemic that has caused the worst economic crisis since the Great Depression. Although the effects of COVID-19 on financial markets were mitigated by massive intervention by central banks in developed countries, global cooperation in this area was much weaker than after the North Atlantic financial crisis. It is concluded: to change and turn in the opposite direction these mass tendencies, the UN system must become the forum for the great political agreement, having the important meaning for reach these ambition development plans agreed in 2015. It was recommended: firstly, to develop more enhanced mechanisms for cooperation with developing countries, not only in the field of health, but also to manage the negative socio-economic consequences of the COVID-19 crisis; secondly, re-new commitments to strengthen trade multilateralism and overcome ...